Characterization and modelling of the rheological behaviour of blended cements based on mineral additions - Bouglada, Mohamed-salah; Naceri, abdelghani; Behhedi, Mohamed; Pereira-de-Oliveira, Luiz (European Journal of Environmental and Civil Engineering, 2019)
This paper presents an experimental study to evaluate the effect of local mineral additions (pozzolan, slag and limestone) on the rheological behaviour of based cement binder’s pastes. The binary, ternary and quaternary binder pastes were prepared with the partial clinker cement replacement limited up to 20%, according with type CEM II specifications. The cements were characterized by their geometric shapes, the reactivity and the chemical composition. An experimental design plan was used to modelling the rheological behaviour of pastes. The relatives yield stress and plastic viscosity of binder’s pastes, with normal consistency, were determined. The results showed that all the tested compositions with additions follow the same rheological behaviour law according to the Bingham model. The binder pastes rheological parameters (yield stress and viscosity) are affected by mineral additions. The highest values of the rheological parameters were measured in binary and ternary cements with limestone and pozzolan. On the other hand, the lower viscosity among the tested pastes was obtained with slag addition. The statistical approach allowed us to obtain a satisfactory modelling of viscosity and yield stress with a coefficient of determination R2 = 0.91 and 0.92, respectively and a satisfactory correlation between the viscosity and the water/binder ratio (W/B) for a normal consistency with a coefficient of determination R2 = 0.91.